KEBIJAKAN NASIONAL DALAM BIDANG ENERGI DAN LINGKUNGAN DALAM ADAPTASI DAN MITIGASI PEMANASAN GLOBAL - Mawardi, Ichwanudin (BPPT)
Current human activities have the potential to increase gas caused by the greenhouse effect. Increasing the temperature is not constant, but in the long time scales indicates that there has been global warming. In connection with efforts to save the earth from climate change in poor countries in the world through the UN session held in Bali have agreed to: (1) Bali Roadmap; (2) agreement on action to perform activities of adaptation to the negative impacts of climate change. Many people who took out the activities of carbon dioxide, kloroflorometan, nitrogen oxides, methane, aerosols, and heat or clearing land for housing, agriculture or logging. The greenhouse effect in nature has been going on for billions of years. Without water vapor and CO2 in the atmosphere,the temperature of the earth will be cooler 33 ° C compared to the current condition, so the earth becomes unfit for habitation. Thus, the greenhouse effect caused by water vapor and CO2 has a positive effect for human life. The problem right now is a greenhouse gas concentrations increasing beyond normal levels of natural as well as the emergence of several new greenhouse gases such as CFCs and CFC successors, which would cause further warming and increasingly threatening the environment carrying capacity. The world has undergone changes in temperature, season, and also increased the frequency of the most dramatic climate that requires continuous regulation to control the global climate system strictly.Keywords: greenhouse effect, global warming, climate change